2016
DOI: 10.1007/s13644-015-0237-y
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Civic Participation and Efficacy in Two Evangelical Protestant Churches

Abstract: This research note examines the proposition that participation in church—particularly the social interaction that accompanies church participation—is an important source of social capital that promotes civic activity and efficacy. Employing survey data from over 600 attendees of two evangelical Protestant churches, we tested hypotheses linking churchgoers’ social networks to their levels of civic efficacy and participation. Three key findings emerged. First, the number of friends in church was positively assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…Thus, the more socially embedded these Evangelicals are in their congregation, the more they are involved in religious volunteering and the less they are involved in secular volunteering. This finding is opposite to the finding of Schwadel et al (2016), we already referred to in the Introduction, who showed for two American evangelical congregations that more extensive in-church social networks positively affect both the congregants' religious and secular civic activities. However, as a minority group Dutch evangelicals are far more urged to uphold a countercultural identity than their American co-religionists are, which probably strengthens their orientation towards their own in-group at the cost of their orientation towards society at large.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Thus, the more socially embedded these Evangelicals are in their congregation, the more they are involved in religious volunteering and the less they are involved in secular volunteering. This finding is opposite to the finding of Schwadel et al (2016), we already referred to in the Introduction, who showed for two American evangelical congregations that more extensive in-church social networks positively affect both the congregants' religious and secular civic activities. However, as a minority group Dutch evangelicals are far more urged to uphold a countercultural identity than their American co-religionists are, which probably strengthens their orientation towards their own in-group at the cost of their orientation towards society at large.…”
Section: Discussioncontrasting
confidence: 98%
“…Furthermore, these small group activities also strengthen friendship bonds within the congregation, which may limit the propensity of evangelicals to engage in secular and non-church activities (Iannaccone 1994;Schwadel 2005). Although there is some evidence that extensive in-church social networks may also promote secular civic activities among evangelicals in the USA (Schwadel et al 2016), with regard to the Netherlands we assume that evangelicals who are socially integrated in their congregation will be especially inclined to engage in religious volunteering. Consequently, our next hypothesis reads: Evangelicals will be more involved in religious volunteering than mainline Christians and non-church members, because they have friends who attend the same congregation and/or because they consider their fellow church group members as friends (hypothesis 3a).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analyzed data, it is obvious that the posts on her Facebook page, which focus on family-related religious topics, are among the most appreciated. As well as researchers argued that religious networks can facilitate volunteerism and civic engagement (McClure, 2015;Merino, 2013;Schwadel et al, 2015), this study revealed that the religious messages published by the Mayor of Bucharest on her Facebook page made her fans to commit and to interact positively concerning religious ideas and values that she promotes. This leads also to a certain civic engagement.…”
Section: Discussionmentioning
confidence: 62%
“…A robust literature demonstrates that relationships within a congregation are related to a host of outcomes. For example, research generally shows that reporting more friends or more close friends in one's congregation is associated with (a) greater religious attendance (Stroope, 2012); (b) greater personal well-being (Lim & Putnam, 2010), belonging (Mammana-Lupo, Todd, & Houston, 2014), and social support (Ellison & George, 1994); (c) more volunteering (Becker & Dhingra, 2001); (d) greater civic and political engagement (Lewis, MacGregor, & Putnam, 2013;Putnam & Campbell, 2010;Schwadel, Cheadle, Malone, & Stout, 2016); and (e) greater social justice engagement (Houston & Todd, 2013;Todd & Allen, 2011). Viewed from social settings theory, these results are in line with the idea that participation in the setting is connected to relationships and that relationships are linked to setting outcomes such as promoting well-being.…”
Section: Relationships and Religious Congregationsmentioning
confidence: 99%